2009
DOI: 10.1038/jcbfm.2009.15
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Profile of the Transcriptome Changes Induced in the Choroid Plexus by Peripheral Inflammation

Abstract: The choroid plexus, being part of the blood-brain barriers and responsible for the production of cerebrospinal fluid, is ideally positioned to transmit signals into and out of the brain. This study, using microarray analysis, shows that the mouse choroid plexus displays an acute-phase response after an inflammatory stimulus induced in the periphery by lipopolysaccharide (LPS). Remarkably, the response is specific to a restricted number of genes (out of a total of 24,000 genes analyzed, 252 are up-regulated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(128 citation statements)
references
References 42 publications
5
122
0
Order By: Relevance
“…CP epithelial cells from rats or mice pups were used to determine the response to Ab. CP epithelial cells were prepared as described elsewhere, 49 with minor modifications. Briefly, neonates (P5-P7) were killed and the CP dissected from the four brain ventricles, under a conventional light microscope (SZX7, Olympus, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…CP epithelial cells from rats or mice pups were used to determine the response to Ab. CP epithelial cells were prepared as described elsewhere, 49 with minor modifications. Briefly, neonates (P5-P7) were killed and the CP dissected from the four brain ventricles, under a conventional light microscope (SZX7, Olympus, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Such an approach has already been performed in adult mice [89] and rats [111]. To the best of our knowledge, the only prenatal study comparing choroid plexuses according to their localization during development was performed in a unique stage of mouse fetuses (E18.5) [85].…”
Section: Understanding Choroid Plexus Developmentmentioning
confidence: 99%
“…5c). Indeed, the choroid plexus transcriptome, proteome, and secretome are dynamic and rapidly change in response to external cues, such as inflammation [89,155]. Choroid plexus epithelial cells have many villi, providing a large surface area for detection of signals in the CSF.…”
Section: Sensor and Modulator Of Physiological States In The Adultmentioning
confidence: 99%
“…The integrity, paracellular permeability and polarization of epithelial cells, in which the BCSFB is localized, depend on the expression of tight junction (TJ) proteins (Wolburg and Lippoldt, 2002). Studies on mice demonstrated that LPS can affect the integrity of the BCSFB by down-regulation of TJ protein expression which could alter interactions between circulating and central mediators (Marques et al, 2009a). In ewes, the amount of TJ proteins in the choroid plexus is modulated by photoperiod -higher during short than long days (Lagaraine et al, 2011), which suggests a potential photoperiodic differentiation of LPS effect on TJ protein expression in the choroid plexus of ewes.…”
Section: Direct Action Of Lps On the Gnrh/lh Secretion The Blood-braimentioning
confidence: 99%